지역사회 거주 노인의 우쿨렐레를 활용한 음악 프로그램 개발 및 효과 - 강경혜(Kang, Gyeong Hye); 제남주(Je, Nam Joo) (지역사회간호학회지, 2021)
Purpose: This study is a pseudo-experimental study of design before and after the non-equivalent control group, which was attempted to verify that the application of the ukulele to the elderly has the effects of reducing depression, improving self-efficacy, strengthening social bonding, and improving cognitive function. Methods: 46 (23 in the experimental group and 23 in the control group) participants were selected. The experimental group was provided with three sessions of a music program using eight Ukuleles for the elderly, while the control group was provided with three sessions for the elderly. IBM SPSS 25.0 was used for data analysis, and the independent t-test, 2-test, and Fisher's exact probability test were performed to verify the homogeneity of the subject's general characteristics. The effect verification after the experimental treatment was analyzed by Fisher's exact probability test, Friedman test, and Mann-Whitney U test. Results: Depression showed a statistically significant difference between the two groups (F=39.88, p<.001), self-efficacy showed a statistically significant difference between the two groups (z=-4.96, p<.001), social bonding showed a statistically significant difference between the two groups (z=-5.19, p<.001), and cognitive function showed a statistically significant difference between the two groups (z=-3.98, p<.001). Conclusion: It was found that the 'Music Program using the Ukulele' was effective in reducing depression of the elderly, improving self-efficacy, reinforcing social bonding, and improving cognitive function. We hope that the Music Program using the Ukulele can be used in the elderly nursing curriculum in the future, and we suggest it should be applied as a nursing intervention to those who are experiencing cognitive decline.